Mechanism of Alkaline Surfactant Polymer in Oil-Water Interface: Physicochemical of Fluid Rheology, Interfacial Tension and Molecular Dynamics Simulation - Numin, M.S. (Springer Science and Business Media B.V., 2021)
Chemicalâs injection such as alkaline, polymer, and surfactant in Chemical Enhanced Oil Recovery (CEOR) can improve oil recovery by modifying the injected fluid characteristics to enhance interaction with oil in the reservoir. The alkaline surfactant polymer (ASP), which consists of 0.3Â M S672 cocamidopropyl betaine derivative surfactant, 1.0Â M sodium carbonate (Na2CO3), and 1000Â ppm hydrolyzed polyacrylamide (HPAM) polymer has good rheological and most shear-thinning properties, better viscoelastic, and most stable emulsion with the highest viscosity. Interactions were investigated using the molecular dynamics (MD) simulation approach by simulating surfactant molecules at the oil-water interface to determine interfacial tension (IFT). Experimentally measured IFT values demonstrate that 0.3Â M S672 concentration has the lowest surfactant value of 0.04Â mN/m and predicted IFT was calculated using the GROMACS software. The behaviors of surfactant molecules at the interface were captured after the simulation to investigate the interface behaviors. The density and IFT values of pure octane with SPC water were 712.95Â kg/m3 and 47.072Â mN/m, respectively, showing excellent agreement with the experimental findings. Increasing surfactant concentration at the oil-water interface has lowered IFT values from 37.20 to 19.07Â mN/m, indicating that surfactant molecules adhered correctly at the interface. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.